2000
DOI: 10.1016/s0014-5793(00)02113-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional similarities between HIV‐1 reverse transcriptase and the Escherichia coli RNA polymerase β′ subunit

Abstract: Four monoclonal antibodies (MAbs) recognizing HIV-1 reverse transcriptase (RT) were shown here to crossreact with the L LP P subunit of Escherichia coli RNA polymerase (RNAP). The anti-RT MAbs bind to a peptide comprising residues 294^305 of the RT amino acid sequence. Computer analyses revealed sequence similarity between this peptide and two regions of the RNAP L LP P subunit. MAb-binding studies using RT mutants suggested that the epitope is located to amino acids 652^663 of the L LP P sequence. One of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Results revealed that the most potent of the studied compounds had IC 50 in the range of 3.3–18.5 µM against the HIV-1 wild-type, making them a good starting point for developing antiretroviral drugs. In turn, bacterial RNA polymerase (RNAP), a proven target for broad-spectrum antibacterial therapy [ 7 , 8 , 9 ], is structurally and functionally similar to reverse transcriptase (RT) [ 10 ]. Consequently, it is reasonable to suppose that our NNRTIs should also inhibit RNAP.…”
Section: Introductionmentioning
confidence: 99%
“…Results revealed that the most potent of the studied compounds had IC 50 in the range of 3.3–18.5 µM against the HIV-1 wild-type, making them a good starting point for developing antiretroviral drugs. In turn, bacterial RNA polymerase (RNAP), a proven target for broad-spectrum antibacterial therapy [ 7 , 8 , 9 ], is structurally and functionally similar to reverse transcriptase (RT) [ 10 ]. Consequently, it is reasonable to suppose that our NNRTIs should also inhibit RNAP.…”
Section: Introductionmentioning
confidence: 99%
“…Although no conclusive information on the shape of the RT of AMV exists to date, it is possible to infer the tertiary structure from similarities with that of other retroviruses such as the RT of HIV-1, which is also a heterodimeric enzyme with two subunits [29]. Earlier STM observations of the HIV-1 RT have shown a rather circular molecule with an opening and a central depression [30].…”
Section: Enzyme-surface Interactionsmentioning
confidence: 99%
“…Steric forces could also play a role. It is well known that RTs are conformationally flexible molecules with the ''fingers'' and ''thumb'' in an open conformation on binding a template primer [29]. As RTs approach the structured silicon surface such conformational changes may allow the enzyme to lock onto Si surface sites.…”
Section: Enzyme-surface Interactionsmentioning
confidence: 99%
See 2 more Smart Citations